Forest degradation modifies litter production, quality, and decomposition dynamics in Southern temperate forests - Leal, Fabiola; Aburto, Felipe; Aguilera, Natalia; Echeverría, Cristian; Gatica-Saavedra, Paula (Frontiers in Soil Science, 2023)
Anthropic disturbances are driving unprecedented changes in forest ecosystem functions and biogeochemical processes, hindering the forests' benefits to society. Litter decomposition is one of the most critical processes that regulate forests’ carbon and nutrient cycling. However, how degradation affects litter decomposition and elemental dynamics needs further examination. The main objective of this study was to evaluate the effect of forest degradation on the production and decomposition of litter and C:N:P stoichiometry dynamics in a temperate forest in south-central Chile. Litter traps and litter bags were installed in three Long Term Research Forest Plots (LTER) representing different conservation states: mature, secondary, and degraded Nothofagus forests. The total litter input varied between 3.5 to 1.1 Mg ha⁻¹ year⁻¹ in the mature and degraded forests, respectively. We found the highest lignin and nutrient levels in the degraded forest and the lowest in the mature forest. In the mature forest, 44% of the initial litter was decomposed, while in the degraded forest, it only reached 7%. Decomposing litter showed the lowest C:N and C:P ratios in the mature forest during most of the year. The balance between inputs and outputs yielded a more substantial litter accumulation in the mature forests. Our results strongly suggest that anthropogenic degradation altered litter quality and nutrient dynamics while decreasing litter production and decomposition.